Morphological peculiarities of tissues in the area of interbody fusion in experimental modelling in rats - Petrenko, Dmytro; Ashukina, Nataliya; Ivanov, Gennadiy; Mezentsev, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article describes results of an experimental study of morphological peculiarities in the area of interbody fusion in the conditions of the fixing of vertebral bodies with a plate after removal of an intervertebral disk. The experiment was made on the caudal spine of 6 laboratory rats. It was revealed that in order to achieve interbody fusion it was necessary to perform total diskectomy in combination with resection of the vertebral end plates.